How to assess a university campus planning — a case study based on students’ spatio-temporal behavior - Weiwei Wang; Feng Zhen; Yang Cao; Yuyao Wang; Yagen Ou (Journal of Asian Architecture and Building Engineering, 2025)
The planning of university campus directly impacts students’ quality of study and living, and there is a considerable amount of research on campus planning assessment, most of which uses post-occupancy evaluation methods. This paper tries to propose a new comprehensive assessment method for campus planning, which collects spatio-temporal behavioral data of students in their daily life through GPS software, then assesses the actual effect of campus planning comprehensively by analyzing the spatio-temporal behavioral characteristics of students. This paper also verifies the reliability of the student behavior characteristics analysis through questionnaire and explores the possible biases. The results indicate that, in addition to significant advantages in reliability, accuracy, and comprehensive judgment, the proposed method can visually reflect specific issues existing within tangible campus spaces and their impact on student behavior. Therefore, it can provide practical and reliable evidence for the practice of campus planning renewal. This method used in this paper is also applicable to other fixed group living spaces within a certain scale, like communities and neighborhoods.